(untitled) (International Journal of Engineering and Computer Science, 2015)
- In this paper, we propose a new hybrid approach between the geographic greedy mode and the recovery mode in order to improve routing efficiency in number of hops, without network overhead. It exploits the optimal topological route to base stations, obtained by beacon messages, as a resource to find better routes than the ones created by greedy mode and recovery mode. We show by simulations that the proposed hybrid approach leads to a significant improvement of routing performance when applied to combined greedy and recovery routing algorithms.